Fighting with their back to the wall: An analysis of one-sided elimination games in National Basketball Association (NBA) playoffs - Morgulev, E.; Raphaeli, M.; Goldschmied, N. (Journal of Sports Sciences, 2022)
In the current study we have used 25 seasons of National Basketball Association (NBA) playoffs and regular season data in order to study human performance under varied incentives. Namely, we have focused on "must win or go home" playoff games to determine if the high pressure experienced by the team playing with its back to the wall (i.e., one-sided elimination game) will boost or undermine performance. Extending existing research, we identified 456 one-sided elimination games, we accounted for regular season performance and controlled for the relative strength of the teams. Our analysis of 11 game parameters failed to observe the anticipated boosting "back to the wall" effect, nor have we detected an overwhelming choking. Instead, current results suggest that when the stakes are already high (i.e., playoffs), additional pressure induced by being in a "back to the wall" situation is only slightly detrimental.